Rapid Detection Method of GMO (Genetically Modified Organism) Content in Soybeans Using an Acid-Base Reaction Approach: A Physico-Chemical Experimental Study (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aimed to develop a simple acid-base reaction-based screening method for distinguishing between GMO (Genetically Modified Organism) and non-GMO soybeans as a practical alternative to expensive and expensive molecular methods. Twenty GMO soybean samples, 20 non-GMO samples, and three mixtures with ratios of 10%, 25%, and 50% were analyzed using 0.01–0.1 N HCl and 0.1 N NaOH solutions. Observation parameters included color change, pH, and absorbance using a UV-Vis spectrophotometer. The results showed that at a concentration of 0.01 N HCl, the color difference was most pronounced. The GMO sample solution showed a red color, while the non-GMO sample solution showed a green color. At higher concentrations, the differences became more subtle or difficult to distinguish. Validation using a PCR assay as the gold standard yielded sensitivity, specificity, and accuracy of >95%, indicating the reliability of this method as an initial screening technique. This physicochemical approach is considered effective for rapid, inexpensive, and easily implemented screening in food industry laboratories, particularly for monitoring non-GMO soybean raw materials and preventing food fraud. Therefore, this acid-base method has the potential to be a practical alternative solution for industry and education in detecting indications of GMOs before further confirmation with molecular methods.